Emergence of Exhausted B Cells in Asymptomatic HIV-1-Infected Patients Naïve for HAART is Related to Reduced Immune Surveillance - Manuela Fogli; Carlo Torti; Fabio Malacarne; Simona Fiorentini; Melania Albani; Ilaria Izzo; Cinzia Giagulli; Fabrizio Maggi; Giampiero Carosi; Arnaldo Caruso (Clinical and Developmental Immunology)
Alterations of B cell subpopulations have been described up to date as characterizing advanced stage of HIV-1 infection. However, whether such defects are relevant in subjects with a preserved number of CD4+ T cells (>350 cells/μL) is unclear. In a cross-sectional study, we investigated if signs of B cells exhaustion and impaired viral immune surveillance are present in a cohort of 43 asymptomatic HIV-1-infected patients with preserved CD4+ T cell counts (>350 cells/μL) and highly active antiretroviral therapy (HAART) untreated. A dramatic expansion of exhausted tissue-like memory B cells (CD10-CD21lowCD27-) was observed. B cells alteration was related to an increase in Torque teno virus (TTV) load, used as surrogate marker of immune function. Successfully HAART-treated patients showed normalization of B cell subpopulations frequency and TTV load. These results provide new insights on B cell in HIV-1 infection and show that development of B cell abnormalities precedes CD4+ T cell decline.